Bridging the divide between scientists and decision-makers: how behavioural ecologists can increase the conservation impact of their research?. (16th September 2019) - Durant, Sarah M.; Groom, Rosemary; Kuloba, Bernard; Samna, Abdoulkarim; Muzuma, Uakendisa; Gadimang, Phemelo; Mandisodza-Chikerema, Rose; Ipavec, Audrey; Mitchell, Nicholas; Ikanda, Dennis; Msuha, Maurus
Abstract : Effective conservation management is underpinned by science. Yet, there are often barriers against the incorporation of up-to-date scientific research into decision-making and policy. Here, we draw on experience from a multi-nation approach to conserve cheetah and African wild dogs across Africa, using relationships between scientists and managers established over more than a decade, to better understand scientific information needs of managers. While our analysis focuses on Africa, many of our findings are likely to be relevant to other regions. Managers view science as critical to their decision-making processes and strongly support scientific research, particularly when research directly addresses their information needs. However, managers reported problems in accessing final results and highlighted the need to access raw ecological data from research undertaken within protected areas. Fundamental to improving the management relevance of scientific research is the need for scientists to engage with managers through all steps of the research process, from project design and implementation through to scientific publication and end-of-project agreements. Effective engagement requires open and clear communication; including agreed processes for access to biodiversity data and submission of final results. In order to foster future scientific endeavours and collaborations, systems should be established to better facilitate information exchange, while also safeguarding the rights of scientists to publish their data and protect their academic freedom. Our analysis also calls for a greater awareness of the geo-political context under which science is undertaken, and for increased scientific participation through an inclusive approach that recognizes, and gives credit to, a wider diversity of scientific contributions and expertise. This article is part of the theme issue 'Linking behaviour to dynamics of populations and communities: application of novel approaches in behavioural ecology to conservation'.